Health Data Linkage for UK Public Interest Research: Key Obstacles and Solutions. (2019) - Mourby, Miranda Jane; Jones, Kerina H; Gilbert, Ruth; Aidinlis, Stergios; Smith, Hannah; Bell, Jessica; Dutey-Magni, Peter; Kaye, Jane
No abstract available